Synthesis, structures, DNA/protein binding, molecular docking, anticancer activity and ROS generation of Ni(ii), Cu(ii) and Zn(ii) 5, 5-diethylbarbiturate complexes with bis(2-pyridylmethyl)amine and terpyridine. (12th July 2017) - Yilmaz, Veysel T.; Icsel, Ceyda; Suyunova, Feruza; Aygun, Muhittin; Cevatemre, Buse; Ulukaya, Engin
Abstract : Synthesis, structures, DNA/BSA binding affinity, antioxidant and cytotoxic activity, cell death and ROS generation of Ni(ii )/Cu(ii )/Zn(ii ) 5, 5-diethylbarbiturate complexes were reported. Abstract : A series of structurally related Ni(ii ), Cu(ii ) and Zn(ii ) 5, 5-diethylbarbiturate (barb) complexes with bis(2-pyridylmethyl)amine (1–3 ) and terpyridine (4–6 ) were synthesized and characterized using elemental analysis, UV-vis, IR, and ESI-MS. Single-crystal X-ray diffraction analysis showed that all complexes are mononuclear. Interactions of the complexes with DNA and protein were studied in detail using experimental and molecular docking techniques, indicating that all the complexes bind to DNA, exhibiting non-covalent binding specificity for G/C and A/T rich regions via a partial intercalative/groove binding mode, and effectively quench the intrinsic fluorescence of BSA through intermolecular interactions. The Cu(ii ) complexes (2 and5 ) displayed a moderate antioxidant activity. In vitro cytotoxicity of1–6 towards four cancer cell lines was evaluated and compared with that of cisplatin.2 and5 showed potent and selective cytotoxic activity against MCF-7 cells, suggesting that the DNA/BSA binding affinity of both complexes correlates with their growth inhibition effects. Furthermore, both complexes induced apoptosis on MCF-7 cells as revealed using flow cytometry analysis. The cytotoxicity and apoptosis induction exerted by2 and5 were associated with production of reactive oxygen species (ROS).